Atomically Thin Sheets of Lead‐Free 1D Hybrid Perovskites Feature Tunable White‐Light Emission from Self‐Trapped Excitons. Issue 23 (5th May 2021) - Klement, Philip; Dehnhardt, Natalie; Dong, Chuan‐Ding; Dobener, Florian; Bayliff, Samuel; Winkler, Julius; Hofmann, Detlev M.; Klar, Peter J.; Schumacher, Stefan; Chatterjee, Sangam; Heine, Johanna
Abstract: Low‐dimensional organic–inorganic perovskites synergize the virtues of two unique classes of materials featuring intriguing possibilities for next‐generation optoelectronics: they offer tailorable building blocks for atomically thin, layered materials while providing the enhanced light‐harvesting and emitting capabilities of hybrid perovskites. This work goes beyond the paradigm that atomically thin materials require in‐plane covalent bonding and reports single layers of the 1D organic–inorganic perovskite [C7 H10 N]3 [BiCl5 ]Cl. Its unique 1D–2D structure enables single layers and the formation of self‐trapped excitons, which show white‐light emission. The thickness dependence of the exciton self‐trapping causes an extremely strong shift of the emission energy. Thus, such 2D perovskites demonstrate that already 1D covalent interactions suffice to realize atomically thin materials and provide access to unique exciton physics. These findings enable a much more general construction principle for tailoring and identifying 2D materials that are no longer limited to covalently bonded 2D sheets. Abstract : Ultrathin crystals of the 1D organic–inorganic perovskite [C7 H10 N]3 [BiCl5 ]Cl featuring covalent bonds only in one direction are exfoliated down to single layers. The unique 1D–2D structure enables self‐trapped excitons with white‐light emission and an extremely strong shift of the emission energy as a result of the thickness dependence of the exciton self‐trapping.